An unusual case of ileo-uterine fistula discovered after full term normal delivery - Singh, Suneeta; Singh, Sanjay; Sharma, Sanjay; Deepak, Opjinder Singh; Banerjee, Ahijit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Entero-uterine fistula is a very rare type of fistula between the small intestine and the genital tract. They may result from obstetric or gynaecological procedures like post D and C perforation of the uterus. Timely detection and management reduce morbidity and mortality of the patients. We present a case of entero uterine fistula in a lady which was diagnosed on second postnatal day when she complained of passage of stool per vaginum. She had a previous history of mid trimester abortion followed by D and C after which she remained hospitalised for a week for pain abdomen. The diagnosis of this fistula was based on her symptoms and clinical evaluation of passage of intestinal content through the cervix and CT scan finding of gas in the abdomen. Intraoperatively an ileal loop was found adherent to the posterior wall of uterus with large fistula between bowel and the uterus. There was no intraperitoneal faecal contamination. Adherent small bowel was separated from the posterior wall of the uterus and fistula dismantled. Side to side functional end to end anastomosis was done using TLC 75 stapler. Repair of the uterine rent was also done. Post op recovery was uneventful.